Adult secondary hemophagocytic lymphohistiocytosis. Issue 2 (13th October 2020) - Obayo, Antonina; Sharma, Karishma; Mithi, Caroline; Riyat, Malkit; Mwirigi, Anne
Abstract: Background: Hemophagocytic lymphohistiocytosis (HLH) is a syndrome of excessive inflammation and tissue destruction due to abnormal immune activation. HLH carries a very high mortality, and while delays in patients' presentation to hospital, time to suspicion of HLH, investigation, and initiation of therapy all play a part, mortality remains high even with timely diagnosis and treatment. Classical manifestations of HLH include persistent fever, cytopenias, and liver dysfunction. Case presentation: We present four cases of secondary HLH, highlighting the demographic and clinical characteristics of these patients, underlying triggers (including systemic lupus erythematosus, lymphoproliferative disorders, and leishmaniasis), together with challenges associated with the diagnosis and treatment of this rare disorder and a brief review of literature. Conclusion: HLH has protean manifestations and requires a high index of suspicion as it can be a great clinical masquerader. Mortality due to multiorgan failure is often high even with early recognition and treatment.